PROTECTION OF LABOR RIGHTS OF EMPLOYEES BY THE STATE LABOR INSPECTION IN UZBEKISTAN - Raximov Miryoqub Aktamovich (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article analyzes the activities of state labor inspectors who protect the labor rights of employees. The problems of labor law enforcement are identified, and suggestions for its improvement are formulated. The purpose of the article is to investigate the problem of protecting the labor rights of employees through the State labor Inspection of the Ministry of employment and labor relations of the Republic of Uzbekistan.